Intracellular Carbonic Anhydrase Activity Sensitizes Cancer Cell pH Signaling to Dynamic Changes in CO(2) Partial Pressure - Hulikova, Alzbeta (American Society for Biochemistry and Molecular Biology, 2014)
Carbonic anhydrase (CA) enzymes catalyze the chemical equilibration among CO(2), HCO(3)(−) and H(+). Intracellular CA (CA(i)) isoforms are present in certain types of cancer, and growing evidence suggests that low levels correlate with disease severity. However, their physiological role remains unclear. Cancer cell CA(i) activity, measured as cytoplasmic CO(2) hydration rate (k(f)), ranged from high in colorectal HCT116 (∼2 s(−1)), bladder RT112 and colorectal HT29, moderate in fibrosarcoma HT1080 to negligible (i.e. spontaneous k(f) = 0.18 s(−1)) in cervical HeLa and breast MDA-MB-468 cells. CA(i) activity in cells correlated with CAII immunoreactivity and enzymatic activity in membrane-free lysates, suggesting that soluble CAII is an important intracellular isoform. CA(i) catalysis was not obligatory for supporting acid extrusion by H(+) efflux or HCO(3)(−) influx, nor for maintaining intracellular pH (pH(i)) uniformity. However, in the absence of CA(i) activity, acid loading from a highly alkaline pH(i) was rate-limited by HCO(3)(−) supply from spontaneous CO(2) hydration. In solid tumors, time-dependence of blood flow can result in fluctuations of CO(2) partial pressure (pCO(2)) that disturb cytoplasmic CO(2)-HCO(3)(−)-H(+) equilibrium. In cancer cells with high CA(i) activity, extracellular pCO(2) fluctuations evoked faster and larger pH(i) oscillations. Functionally, these resulted in larger pH-dependent intracellular [Ca(2+)] oscillations and stronger inhibition of the mTORC1 pathway reported by S6 kinase phosphorylation. In contrast, the pH(i) of cells with low CA(i) activity was less responsive to pCO(2) fluctuations. Such low pass filtering would “buffer” cancer cell pH(i) from non-steady-state extracellular pCO(2). Thus, CA(i) activity determines the coupling between pCO(2) (a function of tumor perfusion) and pH(i) (a potent modulator of cancer cell physiology).